ANALISIS RISIKO PAPARAN PB PAOA MAKANAN JAJANAN PINGGIR JALAN 01 SO PUCANG KOMPLEK KABUPATEN SIOOARJO - Vivin Elvionita; Siti Surasri; Rachmaniyah . (GEMA LINGKUNGAN KESEHATAN, 2013)
Roadsidefoods sold in Pucang complex elementary school pose risks of lead exposure,but children liked them. These childrena population at risk, in fact they have been exposed tolead, therefore their intellectual dexterity can be severely affected. The extent of lead exposurecan be analyzed to estimate whether or not such food is safe for consumption within a certainperiod of time. Therefore, this study aimed to carry out a risk analysis of lead exposure uponroadside food in SD PucangComplex Sidoarjo.This is an exploratory descriptive study. The population are all roadside foods sold inPucangelementary school especially beside JI. Ahmad Yani. Samplesconsisted of roadside foodthat has been exposed for 2 hours. Data were analyzed descriptively by finding RQvalues fromthe calculated intake.The results of lead examination in roadside food discovered as much as 8.288 ppm inbatagor, 6.637 ppm in siomay and 3.751 ppm in meatballs. Following analyses of theseexposures, a minimum intake of 20 mg/ kg.day and a maximum intake of 44.2 mg/ kg.day. Inthe risk characterization stage, RQminimum value of 2.108 and RQmaximum value of 4,42.108were obtained. The study concluded that the concentration were not safe for consumption. Riskmanagement strategy was carried out by calculating safe concentration limit of lead at theamount of 1,875. 10-8 mg/gr.day and the limit for safe consumption rate of lead at the amountof 1.8. 10-7 gr/ day. Meanwhile, the risk management means consisted of technologicalapproach, socia-economicapproach, and institutional approach.Therefore it is advisable to initiate training for vendors, use of food cover, conductfollow up research and disseminate information on the dangers of contaminated roadside foodto students of Pucangelementary school.Keywords : Lead, roadside foods, risk analysis, SO Pucang Complex